Role of Nisha-amlaki In PCOS: A Conceptual Study - Alha, Swati; Kumar, Mahesh; Dave, Hetal H (International Research Journal of Ayurveda & Yoga, 2019)
Introduction: Polycystic ovarian syndrome (PCOS) is characterised by excessive androgen production which interferes with the reproductive, endocrine and metabolic functions. PCOS causes hormonal imbalance in women leading to menstrual irregularities, ovulation and fertility problems1. Woman suffering from PCOS can become insulin resistant due to hormonal imbalance. Diabetes mellitus type 2 is a long term metabolic disorder that is characterized by high blood sugar, insulin resistance and relative lack of insulin. Methodology: The efficacy of Nisha-amlaki2(Astang haridya Ch. sth. 12/5) is widely recommended in Ayurvedic texts for normalizing the blood sugar level. Since the pathology of Prameha and PCOS are similar, so in this way we can use drugwhich described in texts in respective to Prameha to normalise blood sugar, also use in PCOS.Conclusion: Thus, this study is aimed at exploring the role of above given Nisha-amlaki in the treatment of PCOS.